Adaptive Vernacular: A Search for Future Houses in Eastern Region of Thailand - Panin, Tonkao; Mokkhasmita, Tanakarn (Nakhara : Journal of Environmental Design and Planning, 2021)
This study aims to explore ways in which contemporary vernacular houses can be created to be responsive to environmental, socio-cultural, and economic conditions. Within the selected three provinces of Chachoengsao, Prachinburi and Nakhon Nayok, our goal was to propose possible prototypes for contemporary vernacular houses that respond to current requirements while still sustaining their regional characteristics. Current problems and changing housing demands were studied along with input from local people. From field surveys and focus groups, the research found that neither “traditional” nor “modern” solutions will suffice, so the prototypes need to strike a balance between these models. Outcomes developed from this study involve house prototypes that are not models to be strictly copied, but possible creative guidelines which allow their owners to truly adapt to and transform for the future.